Visualising daylight for designing optimum openings in tropical context - Dany Perwita Sari (Department of Architecture Faculty of Engineering Universitas Indonesia, 2024)
With the rising concern for global warming, reducing electricity consumption and promoting daylight utilisation for healthier living conditions are among residential buildings' top priorities. The utilisation of natural light for indoor lighting, particularly in tropical countries like Indonesia, provides health benefits and improves psychological well-being. However, the current condition shows that artificial lighting still accounts for the majority of energy consumption in residential buildings and, arguably, the failure to maximise daylighting was largely due to a limited understanding of the design of openings. This paper aims to exemplify how virtualisation can assist designers through simulation tools to better predict and analyse daylight behaviour in indoor conditions through openings, which are oftentimes neglected by designers. Despite technical challenges, such 3D simulations of daylight visualisation can help to determine the best opening strategy. Thus, this paper compares three lighting simulation tools—Dynamic Daylighting, VELUX Daylight Visualizer, and Rhinoceros Grasshopper, showing the optimal visualisation of lighting quality for tropical context. Based on the model's accuracy as well as input quality and output analysis, the simulation tools are examined for their practicality and detailed daylight 3D visualisation output. This study demonstrates how the simulations of daylight visualisation inform not only the visual image of the window design, but also crucial parameters for designing openings. The parameters enable precise quality of simulation, elaborating the optimum design for performance required in tropical context.